Characterization of DNA ADP-ribosyltransferase activities of PARP2 and PARP3: new insights into DNA ADP-ribosylation - Ishchenko, Alexander A; Lavrik, Olga I; Gasparutto, Didier; Biard, Denis; Matkarimov, Bakhyt T; Kutuzov, Mikhail M; Saint-Pierre, Christine; Talhaoui, Ibtissam; Belousova, Ekaterina A; Zarkovic, Gabriella; Zarkovic, Gabriella (Oxford University Press (OUP), 2018)
Poly(ADP-ribose) polymerases (PARPs) act as DNA break sensors and catalyze the synthesis of polymers of ADP-ribose (PAR) covalently attached to acceptor proteins at DNA damage sites. It has been demonstrated that both mammalian PARP1 and PARP2 PARylate double-strand break termini in DNA oligonucleotide duplexes in vitro. Here, we show that mammalian PARP2 and PARP3 can PARylate and mono(ADP-ribosyl)ate (MARylate), respectively, 5′- and 3′-terminal phosphate residues at double- and single-strand break termini of a DNA molecule containing multiple strand breaks. PARP3-catalyzed DNA MARylation can be considered a new type of reversible post-replicative DNA modification. According to DNA substrate specificity of PARP3 and PARP2, we propose a putative mechanistic model of PARP-catalyzed strand break–oriented ADP-ribosylation of DNA termini. Notably, PARP-mediated DNA ADP-ribosylation can be more effective than PARPs’ auto-ADP-ribosylation depending on the DNA substrates and reaction conditions used. Finally, we show an effective PARP3- or PARP2-catalyzed ADP-ribosylation of high-molecular-weight (∼3-kb) DNA molecules, PARP-mediated DNA PARylation in cell-free extracts and a persisting signal of anti-PAR antibodies in a serially purified genomic DNA from bleomycin-treated poly(ADP-ribose) glycohydrolase-depleted HeLa cells. These results suggest that certain types of complex DNA breaks can be effectively ADP-ribosylated by PARPs in cellular response to DNA damage.